Oral and Perioral Adverse Reaction Following Alginate Impression Making: A Rare Case Report - Gamal Mokhtar Alwafi; Refaat Salem Elnajar; Salma Mohammed Al-Huwainat (Journal of Libyan Academy Bani Walid, 2026)
Background: Alginate impression material is widely used in dentistry and is generally considered biocompatible; however, hypersensitivity-like reactions, although rare, have occasionally been reported. Case presentation: This report describes a 56-year-old healthy female who developed a suspected hypersensitivity-related reaction following exposure to alginate impression material. Primary impressions were taken uneventfully, but within one hour the patient reported oral itching and discomfort. After two days, she presented with extraoral erythematous, crusted lesions at the labial commissures and a severe localized intraoral ulcerative lesion involving the mandibular lingual vestibule and floor of the mouth, covered by a fibrinous pseudomembrane. No systemic symptoms were observed. Based on clinical findings and temporal association with alginate exposure, a provisional diagnosis of suspected allergic contact stomatitis and cheilitis was made. Management and outcome: The patient was treated conservatively with antihistamines, topical anesthetic gel, and antiseptic mouthwash, with complete resolution within one week Conclusion: Although uncommon, oral and perioral adverse reactions may occur following exposure to alginate impression materials. The present case suggests a possible association between alginate exposure and mucosal lesions; however, confirmatory allergy testing was not performed. Further investigations are required to establish the exact etiology and immunological mechanism.